O efeito retórico das histórias anedóticas na biopsicografia de Plutarco - Pinheiro, Joaquim (2018)
Plutarch, a Greek biographer of the imperial period (1st and 2nd centuries A.D.), finds support on different occasions in short jokes, in order to describe his Greek and Roman heroes. In a selection of some of these jokes, we intend to analyse the matter, the context and the rhetorical effect that they bring to the narrative and their contribution to the formation of the main characters’ ethos. The texts analyzed show that Plutarch controls the rhetorical potential of chreiai and the contribution of these short episodes to the heroes’ psychological or physical characterization. It should be also noted that Plutarch did not identify, in many cases, the source from which he collected these stories. In the same way, it is not clear who was the author leading him to the use of anecdotes, though an influence of cynical philosophy is to be suspected.